Self-Efficacy or Overconfidence? Comparing Preservice Teacher Self-Perceptions of Their Content Knowledge and Teaching Abilities to the Perceptions of Their Supervisors. Issue 2 (3rd April 2019) - Dassa, Lori; Nichols, Bryan
ABSTRACT: This study investigated how closely related the perceptions of student teachers were to those of the clinical educators and university supervisors who evaluated them in subject-specific content knowledge and teaching ability. Although our initial concern was low teacher self-efficacy, our study found student teachers consistently rated themselves higher than the professionals who evaluated them. Supervisors also had concerns about the students' ability to process anything but top ratings in a constructive way. Our results suggest that our teacher education program may not be instilling enough healthy doubt in many future teachers, helping us better strike the difficult balance between under- and overconfidence.